Pemberdayaan Madrasah Melalui Implementasi Metode UMMI Untuk Peningkatan Pembelajaran Al-Qur’an: Participatory Action Research di MI Maslakul Huda Lamongan - Zainul Fuad; Nafilatur Rohmah (MADINAH, 2025)
This study aims to empower madrasah communities in implementing improved Al-Qur'an learning methods through the Participatory Action Research (PAR) approach. The problem addressed a madrasah which has been unable to optimally implement the 10 UMMI quality pillars despite joining the program in 2018, evidenced by munaqosah passing rates below 50%. This research employed a critical-transformative PAR approach involving 38 participants (principals, teachers, coordinators, committee members, and parents) as co-researchers through four systematic cycles over four months (September-December). Data were collected through participatory observation, focus group discussions (12 sessions), in-depth interviews (25 participants), and documentation. The findings reveal significant improvements in the implementation of the 10 UMMI quality pillars, with average scores increasing from 71.5 (sufficient) to 84.8 (good). The most substantial improvements occurred in learning time allocation (+21 points, 32.3%), coordinator competency (+20 points, 33.3%), and target clarity (+20 points, 28.6%). Munaqosah passing rates improved dramatically to 84.4%. The novelty of this research lies in developing an Islamic values-based participatory empowerment model that integrates shura (deliberation), ta'awun (mutual assistance), and istiqamah (consistency) principles into educational quality management. This model can be replicated in other madrasahs with contextual adaptations, offering a democratic and transformative approach aligned with international quality standards and Islamic educational values, contributing to SDG 4 (Quality Education) implementation in Islamic education institutions